Ecological Justice for Nature in Critical Systems Thinking. (23rd August 2018) - Stephens, Anne; Taket, Ann; Gagliano, Monica
Abstract : The authors of this paper provide a brief overview of the rights‐based literature that has been used to produce mechanisms to acknowledge non‐human agency in critical systems thinking (CST). With consideration of recent studies of plant cognition, we propose that by recasting CST's underlying commitments, we may produce new ontologies and new ways of working with the embedded stakeholders of socioecological systems. While the discursive shifts are simple, to recast 'social awareness' as 'socioecological awareness' and 'human emancipation' to 'emancipation', these changes open up the boundaries, scope and relevance of practice. We see this as a second turn and the next important movement in CST. © 2018 John Wiley & Sons, Ltd.